4CPS-057 Dalbavancina and tedizolid: adequate alternatives for strains with reduced sensitivity to vancomycin, daptomycin or linezolid?. (2nd March 2018) - Navarro, M; Betancor, T; Tévar, E; Calzado, G; Suárez, M; Plasencia, I; Ramos, E; Gómez, E; Ferrer, A; Vera, M; Merino, J
Abstract : Background: We ask if dalvabancina and tedizolid are good alternatives for strains with reduced sensitivity to vancomycin, daptomycin or linezolid. Purpose: To determine the most cost-effective treatment option for GRAM +microorganisms with reduced sensitivity to vancomycin, linezolid or daptomycin, depending on the in vitro activity determined in our hospital. Material and methods: Retrospective study from January 2016 to January 2017. All Gram +strains underwent antimicrobial susceptibility testing using E-test method on Mueller–Hinton E agar, results were ready at 24 hours. The antibiotics tested were vancomycin, linezolid, daptomycin, tedizolid and dalbavancin. Minimum inhibitory concentrations (MIC) were calculated according to CLSI 2016 and EUCAST 2016 criteria. Direct costs were determined taking into account the acquisition costs of the drug. Hospital costs were not considered in the estimated duration of hospitalisation. A total of 56 strains of Gram +cocci were tested: 21 daptomycin-resistant staphylococcus aureus (50% methicillin-resistant staphylococcus aureus (MRSA)), five coagulase negative staphilococci (CoNS) with reduced sensivity to linezolid, one enterococcus faecium with intermediate sensitivity to linezolid, one linezolid-resistant enterococcus faecalis, eight enterococcus faecalis with intermediate sensitivity to linezolid, nineteen vancomicyn-resistant enterococcus faecium and one vancomycin-resistant enterococcus faecalis. Results: One hundred per cent of staphylococcus aureus strains with reduced sensitivity to daptomycin were sensitive to vancomycin, linezolid, dalbavancina and tedizolid. One hundred per cent of CoNS strains with reduced sensitivity to linezolid were also resistant to tedizolid, 20% were resistant to daptomycin and 100% were sensitive to dalbavancina. One hundred per cent of enterococcus faecium with reduced sensitivity to vancomycin were sensitive to tedizolid and linezolid, 95% were resistant to dalbavancina and 70% were resistant to daptomycin The cost/day of treatment assuming a patient weighing 70 kg and preserved renal function for each treatment is: Intravenous linezolid: €5.5/day. Oral linezolid: €2.5/day. Vancomycin: €4.8/day. Intravenous tedizolid: €860/day. Oral tedizolid: €143.3/day. Dalvabancin: €127.8/day. Daptomycin: €92.5/day. Conclusion: Linezolid presents a good cost-effectiveness profile for staphylococcus aureus and enterococcus faecium strains. All strains that were resistant to linezolid were also resistant to tedizolid. In glycopeptide-resistant strains, dalbavancin had a high minimum inhibitory concentration (MIC) but had a low MIC in those strains resistant to daptomycin. Tedizolid is not a cost-effective option against linezolid. In the case of dalbavancina, it would be necessary to take into account the savings in hospitalisation costs to assess its cost effectiveness. References and/or Acknowledgements: Hospital Candelaria. No conflict of interest